DESIGN OF DRAINAGE, RAINWATER HARVESTING, AND DEWATERING SYSTEM - Afifah Ardiani, Astari
Decreasing of land for living with increasing of people is one of the problems in Bandung City. Bumi Someah Apartment, a mixed-use building that operates both as a residence and retail, can be the solution of this problem. This mixed-use apartment, that is located in Cibadak, has 2 apartment towers (each with 6 and 7 floors), retail (3 floors), and 2 basement floors. On this final project, the water resources aspect which includes the analysis of Citepus river, dewatering, drainage, and rainwater harvesting system is designed. This study is done by collecting and processing secondary data along with using related equations and applicable standards. Citepus river, located on the west side of the apartment, has a 3 meters border line, based on the valid regulations. The layout of the building is moved 4,8 meters to the west but the required border line still cannot be fulfilled on all areas. Flood analysis that is initiated by making ITB-2 unit hydrograph shows that the flood discharge is 129,717 m3/s which makes the flood water level 3,707 meters. Based on the collected data, the depth of river is 2,8 m so a 4,4 meters embankment is needed as flood control. Dewatering work on this project needs 44 dewatering wells whose diameter is 0,18 meters, 13 recharge wells whose diameter is 1,4 meters, ten 2,3 m x 0,5 m x 0,5 m rainwater pits, and piezometer points. Drainage system is designed based on the runoff discharge on each path that is obtained from rational method using 2 year-period rainfall. The drainages use concrete precast for ground floor and PVC gutters for 3rd, 4th, 9th, and 10th floor with different dimension for each path. From the result of water needs and availability balance using mass curve method, this apartment needs a 54,2 m3 rainwater harvesting tank to fulfil the needs of unprocessed water which is toilet flush and plant watering. A 1,4 meters-diameter recharge well is also needed to accommodate the overflow from the rainwater harvesting tank and to fulfil the zero delta Q policy.